CURRENT STATUS OF THE CALIFORNIA OYSTER INDUSTRY - Richards, Thomas L.; Taylor, Phillip R. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
The oyster culture operation in Moro Bay is typical of the United States Pacific Coast Crassostrea gigas mariculture industry. Of this Bays 1,000 hectares of marshes, tidelands and channels 400 hectares have been alloted by the State of California for private oyster cultivation. Approximately 180 hectares of this allotment are suitable for bottom and stake culture on a three-year growing cycle. Each year this 60 hectares is planted with cultch shell at the rate of 60 cases of cultch per hectare. Each case contains an average of 1,000 cultch shells with 10 oyster spat per shell. A typical survival rate of 30% yields, 3,000 liters of oyster meat per hectare after 36 months of growth.